Evaluation of microbial flora in chronic tonsillitis and the role of tonsillectomy (Bangladesh Journal of Otorhinolaryngology, 2012)
Objective: To establish a correlation between clinical picture and bacteriological findings in chronic tonsillitis and to study the efficacy of surface swabs in predicting tonsillar core bacteria.Design: A prospective study analyzing microbiological flora of 149 patients with chronic tonsillitis, 17 patients with acute tonsillitis, 34 control patients and 31 postoperative patients of tonsillectomy was conducted. Surface swabs and fine needle aspiration was done from the tonsils under anesthesia just prior to surgery. Excised tonsils were cultured. A postoperative   surface swab was taken in thirty one randomly selected patients three weeks after surgery.Results: Core cultures of 102 out of 149 patients (68%) were positive for pathogenic bacteria. Core pathogenic flora was mono microbial in nature. Staphylococcus aureus was the commonest cultured pathogen. When compared with tonsil core pathogens, surface swabs and fine needle   aspiration showed 77% and 93% correlation respectively. After tonsillectomy, elimination of pathogenic bacteria from the oropharynx was seen in 97% of the patients.Conclusion: Tonsillectomy eradicated pathogenic microflora from the oropharynx in almost in all patients. Surface swabs have a high degree of reliability and are a useful adjuvant investigation to supplement the clinical diagnosis and can be useful for decision making. DOI:http://dx.doi.org/10.3329/bjo.v18i2.11982 Bangladesh J Otorhinolaryngol 2012; 18(2): 109-113